Zonificación ecológica de Pinus caribaea var. hondurensis Barr. y Golf. y Tectona grandis Linn. para Honduras - Salazar, Rodolfo (IICA, San José (Costa Rica), 2014)
Tesis (Mag. Sc.) -- IICA, San José (Costa Rica), 1973